Reducing unwanted thermal gains during the cooling season for a solar heat pipe system. (May 2015) - Robinson, Brian S.; Sharp, M. Keith
Highlights: Four mechanisms and three control strategies for reducing gains were simulated. Valves to turn off the heat pipes and a cover reduced gains most. An overhang was less effective. Tests of a full-scale prototype confirmed reductions with valves and cover. Abstract: The heat pipe augmented solar heating system significantly reduces heating loads relative to other conventional passive space heating systems. However, thermal gains from the system during the cooling season increase cooling loads and tend to increase overall space conditioning loads. The effectiveness of several design modifications and control strategies for the heat pipe wall to reduce unwanted gains was investigated. Computer algorithms were used to simulate four different unwanted gains reduction mechanisms: shading, an opaque cover, a mechanical valve, and switching the elevations of the evaporator and condenser sections to provide heat transfer out of the room during the cooling season. For each mechanism, three different control strategies were evaluated: (1) Seasonal control, for which the prescribed mechanism was deployed at the beginning and removed at the end of the cooling season, (2) ambient temperature-based control, for which the mechanism was deployed if the forecast for the next hour was greater than 18.3 °C (65 °F), and (3) room temperature-based control, for which the mechanism was deployed if auxiliary cooling was required for the previous hour. For the seasonal strategy, a season determination (SD) parameter was defined and results suggested that SD may be a 'universal' parameter that can be applied across a range of climates for quick cooling season assessment. The heat pipe system performed best with ambient temperature-based control strategy, and the cover and valve were the best single mechanisms. Experiments on a full-scale heat pipe wall prototype using valve and cover control mechanisms confirmed significant reductions in unwanted thermal gains with little to no increase in room temperature during the testing periods.